Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10461-012-0248-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Ring Adherence in Sub-Saharan Africa: Expulsion, Removal, and Perfect Use

Abstract: In sub-Saharan Africa, HIV incidence and prevalence remain disproportionately high among women. Vaginal rings (VRs) have been formulated for the delivery of antiretroviral-based microbicides, and their favorable safety and tolerability profiles reported in clinical studies. Although the concept of drug release through a VR has existed since 1970, and VRs have been marketed since 1992 for contraceptive or hormone replacement purposes, VR use as a microbicide delivery system is a novel application. This is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 22 publications
8
62
0
Order By: Relevance
“…Thus, it is reasonable to assume that it will be easier for women to adhere to long-duration IVR delivery systems compared with daily, episodic, or coitally dependent gels. This is supported by the fact that IVRs have seen excellent product demand and commercial success as a form of birth control in high-income countries and are gaining acceptance in low-income countries (7,29).…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it is reasonable to assume that it will be easier for women to adhere to long-duration IVR delivery systems compared with daily, episodic, or coitally dependent gels. This is supported by the fact that IVRs have seen excellent product demand and commercial success as a form of birth control in high-income countries and are gaining acceptance in low-income countries (7,29).…”
Section: Significancementioning
confidence: 98%
“…Simply put, if the course of protective antiretroviral levels does not match the kinetics of viral exposure, PrEP will not be highly effective. This motivates the development of long duration, drug delivery systems such as intravaginal rings (IVRs) that may overcome these limitations by facilitating adherence and providing less variation in mucosal drug levels (7,8).…”
mentioning
confidence: 99%
“…Topical delivery of ARV drugs using intravaginal rings (IVRs) is believed to improve adherence (18) while maintaining sustained mucosal microbicide levels independently of coitus and daily dosing (19). A recent phase 3, randomized, double-blind, placebo-controlled trial involving 2,629 African women evaluating a monthly IVR delivering the nonnucleoside HIV-1 reverse transcriptase inhibitor dapivirine (DPV) showed that this dosing modality can be effective at preventing HIV-1 infection (20).…”
mentioning
confidence: 99%
“…Controlled topical delivery of ARV drugs using intravaginal rings (IVRs) is thought to improve adherence (11) and to provide sustained mucosal levels independent of coitus and daily dosing (12). The delivery of two or more ARV drugs from conventional IVR designs involves significant technological and manufacturing hurdles.…”
mentioning
confidence: 99%